Why Making Promotion after a Burnout Is like Boiling the Ocean - Philippe Sterkens; Stijn Baert; Claudia Rooman; Eva Derous (Institute of Labor Economics (IZA), 2021)
Recent studies have explored hiring discrimination as an obstacle to former burnout patients. Many workers, however, return to the same employer, where they face an even more severe aftermath of burnout syndrome: promotion discrimination. To our knowledge, we are the first to directly address this issue in research. More specifically, we conducted a vignette experiment with 406 genuine managers, testing the potential of the main burnout stigma theoretically described in the literature as potential mediators of promotion discrimination. Estimates reveal that compared to employees without an employment interruption, former burnout patients have no less than a 34.4% lower probability of receiving a promotion. Moreover, these employees are perceived as having low (1) leadership, (2) learning capacity, (3) motivation, (4) autonomy and (5) stress tolerance, as well as being (6) less capable of taking on an exemplary role, (7) having worse current and (8) future health, (9) collaborating with them is regarded more negatively, and (10) managers perceive them as having fewer options to leave the organisation if denied a promotion. Four of these perceptions, namely lower leadership capacities, stress tolerance, abilities to take on an exemplary role and chances of finding another job explain almost half the burnout effect on promotion probabilities.
Keywords: J71; I14; C83; C91; 330; promotion; burnout; statistical discrimination; taste-based discrimination; invisibility hypothesis